A Simplified Procedure for Thromboplastin Calibration -The Usefulness of Lyophilized Plasmas Assessed in a Collaborative Study - Tripodi, A; Chantarangkul, V; Manotti, C; Poggi, M; Braga, M; Akkawat, B; Bucciarelli, P; Mannucci, P M (Thrombosis and Haemostasis, 1996)
The International Sensitivity Index (ISI) of thromboplastins is determined by calibration using fresh plasmas from 60 patients stabilized on oral anticoagulants and 20 healthy subjects. This procedure is demanding, particularly for those who have no easy access to patients. The alternative use of a smaller number of lyophilized plasmas has already been considered, but one important issue, the number of repeated measurements to be carried out, has never been addressed. Two commercial rabbit thromboplastins, A and B, were calibrated in 3 laboratories against CRM 149R. On each of 10 working days, prothrombin times were measured for a different set of 8 fresh plasmas and for the same set of 8 lyophilized plasmas. The ISI values for both thromboplastins were estimated by orthogonal regression on fresh and lyophilized plasmas. The between- and within-laboratory CV values of the estimated ISI were taken as measures of precision of the calibration. In addition, ISI and CV were calculated daily on cumulative results obtained with lyophilized plasmas from day 1 to day 10. The ISI values for both thromboplastins calculated with lyophilized plasmas were not significantly different from those with fresh plasmas (mean of 3 laboratories: 1.42 vs 1.48 for A and 1.22 vs 1.20 for B). The between-laboratory precision of the calibration with lyophilized plasmas was not considerably different from that with fresh plasmas (CV for 3 labs: 5.2% vs 6.8% for A and 0.9% vs 2.2% for B). The ISI estimated with lyophilized plasmas on results of day 1 were not different from those of days 2 through 10. Good within-laboratory precision of the calibration (CV around 2%) was already achieved on day 3. In conclusion, this study shows that lyophilized plasmas pooled from normals and patients on oral anticoagulants can be used as substitutes for individual fresh plasmas to simplify the existing procedure for thromboplastin calibration.